Office versus leisure environments: Effects of surroundings on concentration. (August 2018) - Burmeister, Carolin P.; Moskaliuk, Johannes; Cress, Ulrike
Abstract: Mobile workers perform tasks that require high concentration not only in their traditional office but also within environments that are typically related to leisure (e.g., in a park or in the living room). Because research has shown that surroundings affect cognitive processing, we assume that concentration is different in office versus in leisure environments. We hypothesize that a typical office activates an associated (work-related) schema which in turn positively influences processes that are normally conducted within the environment (e.g., show high concentration in work-related activities in the office). In two studies, we assessed participants' objective and subjective work-related concentration twice, each time once within an office and once within a leisure environment. In study 1 (laboratory), we manipulated environments by means of virtual realities. In study 2 (field experiment), participants were tested within their self-elected, real-life environments. In both studies, results indicated higher work-related concentration when surrounded by an office compared to a leisure environment. Highlights: Work is no longer done exclusively in the typical office but has also become mobile. Typical work environments are associated with working (work concept). Mobile workers also work in surroundings associated with leisure. Cognitive processes are affected by external surroundings. Being in a work-associated environment enhances work-related concentration.